Does integrity matter in BOP ventures?: the role of responsible leadership in inclusive supply chains - Jaén, María Helena (Journal of business ethics, 2021)
Does responsible leadership matter when assembling an inclusive supply chain at the Base-of-the-Pyramid (BOP)? Current literature implicitly assumes that it does not. BOP scholars initially focused on the importance of shaping innovative and disruptive offerings, with radically improved price-performance ratios. Subsequent studies tended to focus on barriers to implementation of large-scale ventures at the BOP. Their common characteristic was the fact that the attributes and roles of the individuals involved were deemed unimportant. If the opportunity was there, provided barriers were removed and the right value proposition was offered, the inclusive venture should take off. We evaluate three cases of leaders who succeeded in building inclusive ventures at the BOP, in contexts marked by institutional voids—where formal markets were weakly structured or nonexistent. Building a viable business under those circumstances entailed two tasks: imagining what is possible and then turning that vision into a reality. We found that, in carrying out those tasks, individuals do matter. Sampled cases show that working with nontraditional partners in inclusive supply chains requires more than aligning material incentives. Our analysis suggests that responsible leadership (RL) with a strong ethical foundation can provide powerful leverage to ensure buy-in and commitment from the various actors involved. We show how RL can impact organizations and external stakeholders through positive upward spirals. Our analysis contributes to the literature on BOP and RL by confirming, extending, and challenging existing knowledge. We propose two novel attributes (catalyst and social innovator) and argue that context matters, influencing how RL is operationalized and defined. Understanding the critical role of RL in the construction of inclusive supply chains adds a critical missing link that sheds light into the micro level of new business creation, development, and consolidation at the BOP.